2003
DOI: 10.1590/s1516-635x2003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different probiotics on broiler carcass and meat quality

Abstract: The present work evaluated the effect of different probiotics on carcass and meat quality of broilers. One thousand and fifty male Cobb chicks were distributed at one day of age in a randomized design with 3 x 2 + 1 factorial arrangement (3 probiotics, 2 levels of probiotics in drinking water and 1 negative control group), using 5 replications with 30 birds. Carcass yield was higher (p<0.05) in control birds. Nevertheless, the groups fed with probiotics showed higher (p<0.01) leg yield at 45 days of age. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
97
6
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 13 publications
27
97
6
9
Order By: Relevance
“…The results indicated that GalliPro ® nutrients did not affect carcass characteristics (Table 6). These results are in agreement with Pelicano et al (2003Pelicano et al ( , 2005 who reported that, carcass and meat quality did not show alteration when the control group was compared to birds fed probiotics, except for leg yield improvement in the latter. Also, study of Toghyani et al (2011) indicated that carcass yield and relative organ weights were not influenced by dietary probiotic and prebiotic.…”
Section: Resultssupporting
confidence: 92%
“…The results indicated that GalliPro ® nutrients did not affect carcass characteristics (Table 6). These results are in agreement with Pelicano et al (2003Pelicano et al ( , 2005 who reported that, carcass and meat quality did not show alteration when the control group was compared to birds fed probiotics, except for leg yield improvement in the latter. Also, study of Toghyani et al (2011) indicated that carcass yield and relative organ weights were not influenced by dietary probiotic and prebiotic.…”
Section: Resultssupporting
confidence: 92%
“…The cut yields were also not affected (p>0.05) by the different additives that were used, similarly to the Pelicano et al (2003) evaluated different probiotics and reported leg yields significantly higher when the products were added to the diet. Therefore, it is suggested that such promoters might be used in broiler diets, since they do not interfere, or interfere positively, on the yield of the most commercialized edible cuts (breast, legs and wings).…”
Section: Resultssupporting
confidence: 55%
“…Therefore, the different additives might be used since they did not affect meat color, which is an extremely important parameter that is related to the choice made by the consumer. Pelicano et al (2003) added probiotics both to the drinking water and to the diet of broiler chickens and observed L* values significantly smaller at 45 minutes and 5 hours after slaughter. The values reported by Pelicano et al (2003) for L*, a* and b* were, respectively, from 49.95 to 48.10; from 4.80 to 4.24 and from 4.98 to 3.80, which are considerably higher than the values found in the present study.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations